Characterization of trading of agroecological holdalls. Case study in La Plata, 2019-2020 (Huellas, 2021)
The trading of holdalls of agroecological vegetables draws attention to the increase of selling these products and social awareness, as the purpose of these holdalls is to lessen the effect of rising prices; especially during the isolation caused by the Covid-19 pandemic. In this context, new spaces multiplied and already existing ones enhanced. This article analyzes the main characteristics of this circuit through a case study in La Plata; more specifically, by analyzing the case of a group of agroecological producers who sells the production through Pueblo a Pueblo system. Variables related to the holdall, such as variety, price construction, the organization rol and its main constraints were considered when applying a qualitative methodology based in a case study. Primary and secondary data were collected. This study provided data in relation to contributions and difficulties this circuit is facing, among which social construction of food trading and subjects active roles are highlighted.
Keywords: trading; bags; agroecology